Examining metallic glass formation in LaCe:Nb by ion implantation - Sisson Richard (Nuclear Technology and Radiation Protection, 2017)
In order to combine niobium (Nb) with lanthanum (La) and cerium (Ce), Nb ions were deposited within a thin film of these two elements. According to the Hume-Rothery rules, these elements cannot be combined into a traditional crystalline metallic solid. The creation of an amorphous metallic glass consisting of Nb, La, and Ce is then investigated. Amorphous metallic glasses are traditionally made using fast cooling of a solution of molten metals. In this paper, we show the results of an experiment carried out to form a metallic glass by implanting 9 MeV Nb 3+ atoms into a thin film of La and Ce. Prior to implantation, the ion volume distribution is calculated by Monte Carlo simulation using the SRIM tool suite. Using multiple methods of electron microscopy and material characterization, small quantities of amorphous metallic glass are indeed identified.